Keterampilan Memberikan Penguatan (Reinforcement) Pada Mata Pelajaran PAI di SMK Negeri 6 Bone - Nurhayati, R; Andra Ningsih, Diarti; P, Sudirman; Muh. Taufiq Nur, A; Kurnia, Sitti; Hidayah, Nur; Fitrawati, Nurul; Khairati, Mismaya (LP2M Universitas Islam Ahmad Dahlan, 2023)
Teaching skills are crucial in the student learning process and should be mastered by educators. The reinforcement aspect of applying teaching skills can be divided into two categories: verbal reinforcement, which includes words or phrases like